2022
DOI: 10.1002/prp2.925
|View full text |Cite
|
Sign up to set email alerts
|

Nonsteroidal anti‐inflammatory drugs in acute viral respiratory tract infections: An updated systematic review

Abstract: In this systematic review, we aimed to assess the efficacy and safety of nonsteroidal anti‐inflammatory drugs (NSAIDs) in treating respiratory tract infections in adults and children. PubMed, Scopus, Web of Science, Cochrane, and Embase databases were searched. A total of 34 randomized clinical trials were included in this systematic review. We assessed the risk of bias of all included studies using the Cochrane tool for risk of bias assessment. The evidence on ibuprofen, naproxen, aspirin, diclofenac, and oth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
7
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 46 publications
0
7
0
1
Order By: Relevance
“… 2 , 5 An updated systematic review showed that in comparison to paracetamol, ibuprofen has a similar effect in fever control and recovery from the common cold in pediatric patients without a significant increase in gastrointestinal discomfort. 60 In a separate trial comprising 84,192 children, adverse events related to ibuprofen use at two differing doses were investigated and the risk of hospitalization for gastrointestinal bleeding or renal failure was found not to increase in comparison to the use of paracetamol. 61 However, although it is relatively safe in terms of other adverse events, ibuprofen is the most frequent cause of NSAID-induced hypersensitivity reactions in susceptible children.…”
Section: Introductionmentioning
confidence: 99%
“… 2 , 5 An updated systematic review showed that in comparison to paracetamol, ibuprofen has a similar effect in fever control and recovery from the common cold in pediatric patients without a significant increase in gastrointestinal discomfort. 60 In a separate trial comprising 84,192 children, adverse events related to ibuprofen use at two differing doses were investigated and the risk of hospitalization for gastrointestinal bleeding or renal failure was found not to increase in comparison to the use of paracetamol. 61 However, although it is relatively safe in terms of other adverse events, ibuprofen is the most frequent cause of NSAID-induced hypersensitivity reactions in susceptible children.…”
Section: Introductionmentioning
confidence: 99%
“…The most commonly used anti-inflammatory drugs are ibuprofen and paracetamol, whose safety profile makes their use widespread even in pediatric settings. Recent reviews examined the effectiveness of these drugs in fever, respiratory tract inflammation, and asthma, and concluded that a similar are rare when used for short periods (less than 7 days) [ 4 , 5 ]. Moreover, a meta-analysis including 19 studies found no significant difference between the two agents in the incidence of adverse events in pediatric patients [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…[19][20][21] Therefore, searching reliable, secure, and natural methods for treatment of COVID and In uenza are continuing in the worldwide. [3,5,17,18,22] NCDs and COVID are spreading in countries with a higher rate of overweight. [10,[23][24][25][26][27] The Comprehensive Assessment of the Long-term Effects of Reducing Intake of Energy (CALERIE) phase 2 trial showed that moderate reduction of energy intake averaging approximately 12% over 2 years could improve markers of in ammation, cardiometabolic health, and oxidative stress in humans.…”
Section: Introductionmentioning
confidence: 99%